Speculation Duopoly With Agreement to Disagree: Can Overconfidence Survive the Market Test? - Kyle, Albert S; Wang, F Albert (Journal of Finance, 1997)
In a duopoly model of informed speculation, the authors show that overconfidence may strictly dominate rationality since an overconfident trader may not only generate higher expected profit and utility than his rational opponent but also higher than if he were also rational. This occurs because overconfidence acts like a commitment device in a standard Cournot duopoly. As a result, for some parameter values the Nash equilibrium of a two-fund game is a prisoner's dilemma in which both funds hire overconfident managers. Thus, overconfidence can persist and survive in the long run.